Freedom to Contract in The Romanian Legal System - Bularca Anca Roxana (Legal Research & Analysis, 2024)
The freedom to contract represents a component of the right to individual freedom, this being a fundamental citizen's right. This right can be exercised, however, under the conditions and with the limits provided by law. In capitalist democratic societies, the contract represents a cell in an infinite labyrinth of legal relations that unfold between the participants in the civil and economic circuit. From this perspective, the contract must be analyzed at the micro level, but also at the macro level. In order to ensure a state of balance and equity at a general level, often the individual freedom to contract can be limited in order to ensure a collective freedom, in order to achieve a common interest, often economic.